14.5 GHz passive harmonic mode-locking in a dispersion compensated Tm-doped fiber laser - Yazhou Wang (Nature Portfolio, 2017)
Abstract We demonstrate a high repetition rate passive harmonic mode-locking (HML) based on nonlinear polarization evolution (NPE) technique in a Tm-doped ring fiber laser cavity. Small net anomalous cavity dispersion based on dispersion compensation benefited the generation of high repetition rate HML due to the low soliton splitting threshold. Stable HML with a repetition rate of up to 14.5 GHz and a super-mode suppression (SSR) of 19 dB was obtained at the center wavelength of 1982.3 nm, which is about ten times of state of the art at 2 μm band mode-locking fiber laser to our best knowledge. The repetition rate was selectable between 1 GHz to 14.5 GHz through changing the pump power and intra-cavity polarization state, and the SSR better than 25 dB was obtained as the repetition rate less than 5 GHz.